Accuracy of LiDAR-based tree height estimation and crown recognition in a subtropical evergreen broad-leaved forest in Okinawa, Japan - Ahmad Zawawi, Azita; Masami, Shiba; Naim Jemali, Nor Janatun (Spanish National Institute for Agricultural and Food Research and Technology, 2015)
Aim of study: To present an approach for estimating tree heights, stand density and crown patches using LiDAR data in a subtropical broad-leaved forest.